Which of the following expressions could you rewrite using the Associative Property?
(9 ⋅ 5) + 8 + 3
(9 ⋅ 5) ⋅ (8 ⋅ 3)
(5 ⋅ 8) + 3
(5 + 8) ⋅ 3
8 answers
The expression that could be rewritten using the Associative Property is: (5 + 8) ⋅ 3.
Which of the following correctly demonstrates the Associative Property of Addition?
x⋅(y+z)=(x⋅y)+z
m⋅(x⋅y)=(m⋅x)⋅y
(x+y)+z+r=x+(y+z)+r
y−(x+1)=(y−x)+1
x⋅(y+z)=(x⋅y)+z
m⋅(x⋅y)=(m⋅x)⋅y
(x+y)+z+r=x+(y+z)+r
y−(x+1)=(y−x)+1
The following expression correctly demonstrates the Associative Property of Addition:
(x+y)+z+r=x+(y+z)+r
(x+y)+z+r=x+(y+z)+r
Use the Associative Property to determine which expression is correctly simplified.(1 point)
Responses
−3 ⋅ (4x ⋅ −2) ⋅ −6y = (−3 ⋅ 4x) ⋅ −2 − 6y
−3 ⋅ (4x ⋅ −2) ⋅ −6y = −7xy
−3 ⋅ (4x ⋅ −2) ⋅ −6y = 18 − 8x
−3 ⋅ (4x ⋅ −2) ⋅ −6y=(−3 ⋅ 4x)(−2 ⋅ −6y)
Responses
−3 ⋅ (4x ⋅ −2) ⋅ −6y = (−3 ⋅ 4x) ⋅ −2 − 6y
−3 ⋅ (4x ⋅ −2) ⋅ −6y = −7xy
−3 ⋅ (4x ⋅ −2) ⋅ −6y = 18 − 8x
−3 ⋅ (4x ⋅ −2) ⋅ −6y=(−3 ⋅ 4x)(−2 ⋅ −6y)
The expression that is correctly simplified using the Associative Property is:
−3 ⋅ (4x ⋅ −2) ⋅ −6y = (−3 ⋅ 4x)(−2 ⋅ −6y)
−3 ⋅ (4x ⋅ −2) ⋅ −6y = (−3 ⋅ 4x)(−2 ⋅ −6y)
According to the Associative Property, which expression is equivalent to 30m+(21m−53)+(18−2m)?
(49m−53)+16
53m−35
(30m+21m)+(18−2m)
51m+(−53+18)−2m
(49m−53)+16
53m−35
(30m+21m)+(18−2m)
51m+(−53+18)−2m
According to the Associative Property, the expression that is equivalent to 30m+(21m−53)+(18−2m) is:
(30m+21m)+(18−2m)
(30m+21m)+(18−2m)
1.( 9•5)•(8•3)
2.(x+y)+z+r=x+(y+z)+r
3.(3•5)•2=3•(5•2)
4.-3•(4x•-2)•-6y=(-3•4x)(-2•-6y)
5.51m+(-53+18)-2m
2.(x+y)+z+r=x+(y+z)+r
3.(3•5)•2=3•(5•2)
4.-3•(4x•-2)•-6y=(-3•4x)(-2•-6y)
5.51m+(-53+18)-2m